The importance for immunoregulation for long-term cancer control. (August 2017) - Fusi, Alberto; Dalgleish, Angus
Immune checkpoint blockades have recently emerged as a breakthrough treatment for solid tumors showing high response rates and long durability. In melanoma, the combination of ipilimumab with nivolumab showed high efficacy. However, still half the patients do not respond to this treatment. In order to increase the therapeutic ratio in melanoma and other cancers, different approaches are under evaluation. Three relevant questions are at the moment driving the research community: how to maximize benefit while minimizing toxicity; how to better identify patients who are more likely to benefit from immunotherapy; how to convert nonresponders into responders. In this review we summarize the most recent findings and we outline the most likely future challenges.